1991
DOI: 10.1073/pnas.88.1.276
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional properties of transforming growth factor alpha and epidermal growth factor during mouse mammary gland ductal morphogenesis.

Abstract: Expression and functional properties of transforming growth factor a and epidermal growth factor during mouse mammary gland ductal morphogenesis ( Communicated by Elwood V. Jensen, October 1, 1990ABSTRACT Primer-directed enzyme amplification was used to examine epidermal growth factor (EGF) and transforming growth factor a (TGF-a) mRNA transcripts in mammary glands of young virgin, mature virgin, midpregnant, and midlactating mice. Transcripts for both EGF and TGF-a mRNA were detected in virgin and pregnant mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(84 citation statements)
references
References 49 publications
3
81
0
Order By: Relevance
“…Although the above genetic evidence indicates that AREG is uniquely required for normal mammary morphogenesis [25], other studies had shown that several EGFR ligands could rescue ductal development in ovariectomized and ERĪ±-deficient mice [26,[31][32][33] and that all EGFR ligands had comparable effects in culture [17,28]. So why were other EGFR agonists unable to compensate for the absence of AREG in vivo?…”
Section: Epithelial Areg Is Essential For Mammary Developmentmentioning
confidence: 99%
“…Although the above genetic evidence indicates that AREG is uniquely required for normal mammary morphogenesis [25], other studies had shown that several EGFR ligands could rescue ductal development in ovariectomized and ERĪ±-deficient mice [26,[31][32][33] and that all EGFR ligands had comparable effects in culture [17,28]. So why were other EGFR agonists unable to compensate for the absence of AREG in vivo?…”
Section: Epithelial Areg Is Essential For Mammary Developmentmentioning
confidence: 99%
“…Signal transduction from the EGFR is initiated when ligand binding stimulates receptor dimerization and tyrosine autophosphorylation on multiple carboxy-terminal tyrosines, which then act as high-affinity binding sites for effector proteins [25]. EGFR signaling pathways regulate proliferation of normal mammary epithelial cells [26][27][28] and of ER(+) hormone-dependent HBC cells [29].…”
Section: Introductionmentioning
confidence: 99%
“…Similar cellular and temporal expression patterns have been documented for EGFR (DiAugustine et al, 1997;Ederly et al, 1985;Sebastian et al, 1998;Schroeder and Lee, 1998), ErbB3 (Sebastian et al, 1998;Schroeder and Lee, 1998;Yang et al, 1995), and ErbB4 (Sebastian et al, 1998;Yang et al, 1995), although the expression of ErbB4 is highest during pregnancy (Schroeder and Lee, 1998). Likewise, the EGFR agonists, EGF (Schroeder and Lee, 1998;Snedeker et al, 1991), TGFa (Schroeder and Lee, 1998;Snedeker et al, 1991), and AR (Kenney et al, 1995;Schroeder and Lee, 1998) are expressed in both virgin and pregnant mammary tissue. In contrast to these ligands, signiĀ®cant expression levels of the ErbB3 and ErbB4 ligand, NRG1, are only detected during pregnancy (Yang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Mammary implants containing EGF (Coleman et al, 1988;Snedeker et al, 1991), TGFa (Snedeker et al, 1991), or AR (Kenney et al, 1996) induce ductal morphogenesis and proliferating terminal end bud (TEB) formation in ovariectomized mice. Consistent with the proliferative e ects of EGFR ligands on mammary development, inhibition of EGFR signaling with a dominant negative EGFR results in decreased ductal proliferation and impaired morphogenesis in the virgin mammary gland (Xie et al, 1997).…”
Section: Introductionmentioning
confidence: 99%